BENTUK PENYAJIAN KESENIAN REOG PONOROGO DI JORONG KOTO AGUNG NAGARI SUNGAI DUO KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - Nika Suryanti; Darmawati Darmawati; Desfiarni Desfiarni (SENDRATASIK UNP, 2017)
AbstrackThe purpose of this research was to describe the Presentation Form of Reog Ponorogo in Jorong Koto Agung Nagari Sungai Duo Sitiung District, Dharmasraya Regency. This was a qualitative research which used descriptive method. This method could fulfill, reveal and document the ways which were used to obtain data in the field. The object of the research was Reog Ponorogo in Jorong Koto Agung Nagari Sungai Duo Sitiung District, Dharmasraya Regency. The instrument of this research was the researcher assisted by stationery and camera. The data were collected by conducting literature study, observation, interview and documentation. The technique of data analysis was the technique of primary data tabulation that was initiated by the fieldwork process to the stage of identifying data in formal themes which were equipped with secondary data. The result of this research was that the presentation form of Reog Ponorogo was non representative. It was seen through the elements of dance presentation that is motion, dancer, floor pattern, music, costume, makeup, property, time and place of the performance. The presentation form of Reog Ponorogo in Jorong Koto Agung Nagari Sungai Duo has 3 forms of dance including Jathilan, Bujang Ganong and Singo Barong. Keywords: Reog Ponorogo and Jorong Koto Agung Nagari Sungai Duo.